Development of MDLC-Based WebAR and WebVR Platforms as Digital Educational Media for Batik Motifs - Muhammad Dedi Irawan; Yusuf Ramadhan Nasution; Yustria Handika Siregar; Muhammad Eka (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: The low interest of the younger generation in Malay hand-drawn batik and the limitations of interactive learning media pose challenges in efforts to preserve local culture. This study aims to develop more attractive and accessible digital educational media through the integration of Web Augmented Reality (WebAR) and Web Virtual Reality (WebVR). Contribution: This activity contributes to providing an immersive web-based cultural education platform that does not require the installation of any applications, so that it can be used by the general public, especially the younger generation and batik SME players, to improve cultural literacy and promotional effectiveness. Method: The approach used was the Multimedia Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, assembly, and testing. The testing phase consisted of alpha testing by experts and usability testing involving 60 young users aged 15–30 years. Results: The usability testing results showed a very good acceptance rate, namely 92% for ease of use, 88% for increased interest in batik, 84% for attractiveness compared to conventional media, and 92% for the usefulness of the application as a promotional medium. Conclusion: The development of the WebAR and WebVR platforms successfully fulfilled the research objectives, namely to provide more attractive, interactive, and accessible digital educational media to increase the younger generation's understanding and interest in Malay hand-drawn batik motifs.